2014
DOI: 10.1371/journal.pone.0093322
|View full text |Cite
|
Sign up to set email alerts
|

Δ12-Fatty Acid Desaturase from Candida parapsilosis Is a Multifunctional Desaturase Producing a Range of Polyunsaturated and Hydroxylated Fatty Acids

Abstract: Numerous Δ12-, Δ15- and multifunctional membrane fatty acid desaturases (FADs) have been identified in fungi, revealing great variability in the enzymatic specificities of FADs involved in biosynthesis of polyunsaturated fatty acids (PUFAs). Here, we report gene isolation and characterization of novel Δ12/Δ15- and Δ15-FADs named CpFad2 and CpFad3, respectively, from the opportunistic pathogenic yeast Candida parapsilosis. Overexpression of CpFad3 in Saccharomyces cerevisiae strains supplemented with linoleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…The synthesis of PUFAs is significantly downregulated in tyrosol-treated cells, as tyrosol decreased the expression of the FAD2 and FAD3 genes encoding delta12-fatty acid desaturase and omega-3 fatty acid desaturase enzymes, respectively. These are orthologs of genes participating in PUFA synthesis in C. albicans (16,17). PUFAs (stearidonic acid, eicosapentaenoic acid, and docosapentaenoic acid) are major components of the cell membrane of C. parapsilosis, accounting for approximately 30% of the fatty acid content, and have a remarkable antioxidant effect (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of PUFAs is significantly downregulated in tyrosol-treated cells, as tyrosol decreased the expression of the FAD2 and FAD3 genes encoding delta12-fatty acid desaturase and omega-3 fatty acid desaturase enzymes, respectively. These are orthologs of genes participating in PUFA synthesis in C. albicans (16,17). PUFAs (stearidonic acid, eicosapentaenoic acid, and docosapentaenoic acid) are major components of the cell membrane of C. parapsilosis, accounting for approximately 30% of the fatty acid content, and have a remarkable antioxidant effect (17).…”
Section: Discussionmentioning
confidence: 99%
“…These are orthologs of genes participating in PUFA synthesis in C. albicans (16,17). PUFAs (stearidonic acid, eicosapentaenoic acid, and docosapentaenoic acid) are major components of the cell membrane of C. parapsilosis, accounting for approximately 30% of the fatty acid content, and have a remarkable antioxidant effect (17). Tyrosol-induced inhibition of the expression of FAD2 and FAD3 found in this study therefore decreases the antioxidant level in cell membranes, which may contribute to the antifungal effect of tyrosol against C. albicans or C. parapsilosis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced phagocytosis and killing of ⌬/⌬ole2 cells and the induced increased levels of interleukin-10 (IL-10) suggested that CpOLE2 may also be involved in virulence regulation (136). Although functional Δ12/Δ15-and Δ15-fatty acid desaturases (FAD2 and FAD3) have also been identified in this species, their influence on virulence has not yet been investigated (228).…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%
“…Yeasts transformed with pYES2 and pYEXTHS-BN were cultivated in liquid YNB medium lacking uracil. Heterologous FAD expression in pYEXTHS-BN transformed yeasts was monitored by Western blotting using anti-His6tag antibodies (37). Total cellular lipids were transesterified to FAMEs (18).…”
mentioning
confidence: 99%